The prediction of early reading performance: a comparative perspective in Spanish and Chilean children - de la Calle Cabrera, Ana María (Revista Complutense de Educación, 2019)
Educational systems incorporate linguistic competences in the educational curriculum at the levels of Early Childhood Education in the international context. Our research raises the need to deepen the comparative analysis of reading performance in Early Childhood Education. This study compares early reading performance and skills in cognitive precursors of reading in a sample of 100 pre-readers from Chile and Spain. The Start-to-Read Battery (Batería de Inicio a la Lectura, BIL), the Rapid Automatized Naming Test (RAN), a verbal fluency test and the revised version of the Battery for the Evaluation of Readers Processes (Batería de Evaluación de los Procesos Lectores, PROLEC-R) are used. The comparative perspective of this study reveals the differences between the cognitive skills and the reading performance of Chilean and Spanish students at early ages. Letters Knowledge is shown as the best precursor of the early reading in Spanish and the hub of the differences in the prediction. Our findings guide for the optimization of reading performance in Spanish since the beginning of schooling in the Chilean and Spanish education systems and motivates the need for Comparative Education in Early Childhood Education.